TRPC5 ion channel permeation promotes weight gain in hypercholesterolaemic mice - Rode, Baptiste; Yuldasheva, Nadira Y.; Baxter, Paul D.; Sedo, Alicia; Ainscough, Justin F.; Shires, Michael; Kearney, Mark T.; Bailey, Marc A.; Wheatcroft, Stephen B.; Beech, David J. (Scientific reports, 2019)
Transient Receptor Potential Canonical 5 (TRPC5) is a subunit of a Ca 2+ -permeable non-selective cationic channel which negatively regulates adiponectin but not leptin in mice fed chow diet. Adiponectin is a major anti-inflammatory mediator and so we hypothesized an effect of TRPC5 on the inflammatory condition of atherosclerosis. Atherosclerosis was studied in aorta of ApoE −/− mice fed western-style diet. Inhibition of TRPC5 ion permeation was achieved by conditional transgenic expression of a dominant negative ion pore mutant of TRPC5 (DNT5). Gene expression analysis in adipose tissue suggested that DNT5 increases transcript expression for adiponectin while decreasing transcript expression of the inflammatory mediator Tnfα and potentially decreasing Il6, Il1β and Ccl2. Despite these differences there was mild or no reduction in plaque coverage in the aorta. Unexpectedly DNT5 caused highly significant reduction in body weight gain and reduced adipocyte size after 6 and 12 weeks of western-style diet. Steatosis and circulating lipids were unaffected but mild effects on regulators of lipogenesis could not be excluded, as indicated by small reductions in the expression of Srebp1c, Acaca, Scd1. The data suggest that TRPC5 ion channel permeation has little or no effect on atherosclerosis or steatosis but an unexpected major effect on weight gain.